Sanksi Pidana Denda Bagi Pelaku Penyalahgunaan dan Pengedaran Gelap Narkotika (Studi Putusan Perkara Nomor 468/Pid.Sus/2024/PN Smg) - Oktaviani, Aghnia Qinthari; Rochmani, Rochmani (Wajah Hukum, 2025)
The illicit circulation and abuse of narcotics in Indonesia constitute a serious and escalating problem that threatens social and economic stability, as well as the future of the younger generation. One form of law enforcement against narcotics traffickers is the imposition of criminal fines as stipulated in Law Number 35 of 2009 on Narcotics. This study aims to explain and analyze the imposition of criminal fines in addressing illicit narcotics circulation and to examine judicial considerations in Case Decision Number 468/Pid.Sus/2024/PN Smg. The method employed is normative juridical research, which examines norms in positive law and court decision studies. Based on the research findings, the imposition of a criminal fine of IDR 1,000,000,000.00 with a subsidiary six-month imprisonment in this case is deemed insufficient to deliver the expected deterrent effect, as the offender may circumvent legal consequences through financial capability or networks within correctional facilities. The judge’s considerations in rendering the decision encompass juridical and sociological aspects; however, further evaluation of the fines is necessary to ensure they create both deterrence and justice. This study underscores the need to strengthen legal instruments so that criminal fines are not merely symbolic but also functional in combating narcotics-related crimes.